PREGNANCY-ASSOCIATED BREAST CANCER: CASE REPORT - Sanvido, Vanessa Monteiro; Simomoto, Mary Miyazawa; Nazário, Afonso Celso Pinto (Mastology, 2020)
Introduction: Mammographic screening is recommended yearly after the age of 40; however, many pregnant women are younger and should undergo the test. In these cases, anamnesis and clinical examination of the breasts are essential to detect any breast change. In case of clinical suspicion, it is recommended to undergo mammography with abdominal protection, and breast ultrasound is the examination of choice to assess the extension of the injury and guide the percutaneous biopsy. Breast surgery is safe, and can be performed in the three trimesters of pregnancy. It is important to emphasize the importance of the type of surgery according to gestational age. The reference axillary surgery during pregnancy is axillary lymphadenectomy. However, some articles present the safety of the sentinel lymph node biopsy. The use of technetium (Tc-99m) with lymphoscintigraphy is an acceptable technique, with fetal exposure to radiation inferior to the teratogenic limit of 50 mGv. Objective: To emphasize the importance of mammary propedeutics during pregnancy. Case report: 37 year-old patient, primiparous, of 34 weeks, referred a nodule in the right breast for 1 year. She denies having family history of carcinoma. At clinical examination, she presented with turgid breasts, absence of palpable nodules and negative axilla. Current mammography with presence of architectural distortion in the inferolateral quadrant of the right breast, and ultrasound with irregular and spiculated 2 cm nodule , both BIRADS category 5. Percutaneous biopsy showed invasive breast carcinoma of no special type, histological grade 2, and immunohistochemical with positive hormone receptors (estrogen and progesterone receptor with 90%), negative HER2 and Ki 67 of 20%> The conduct was conserving surgery (excision of the breast injury and radio-guided sentinel lymph node biopsy) on the 36th week of pregnancy. The intraoperative assessment of the sentinel lymph node showed presence of macrometastasis and, as a consequence of the exclusion of pregnancy in the ACOSOG Z0011 study, the patient was submitted to axillary lymphadenectomy. The defini-tive anatomopathological result was invasive breast carcinoma of no special type, histological grade 3, measuring 2.1 cm, and 1 lymph node compromised by macrometastasis of 15 dissected nodes (pT2 pN1a). The multidisciplinary team chose to wait for delivery, from 2 to 4 weeks, and a Cesarean section was performed after 40 weeks of pregnancy. The chemo-therapy was scheduled to begin 4 weeks after delivery. The patient was referred to genetic counselling. Conclusions: The treatment of breast cancer during pregnancy is challenging for the multidisciplinary team, which must focus on maternal and fetal well-being. Therapy should be carried out similarly to non-pregnant patients, respecting the procedures that are allowed in each gestational trimester. It is important to mention how essential it is to not delay the treatment, in order to not compromise the patient’s prognosis.